2014
DOI: 10.1097/01.nurse.0000456382.63520.24
|View full text |Cite
|
Sign up to set email alerts
|

Does skin care frequency affect the severity of incontinence-associated dermatitis in critically ill patients?

Abstract: The researchers studied a defined skin care protocol using a cleanser with aloe vera and a cleansing lotion, followed by application of either a moisture barrier with silicone or skin protectant with zinc oxide and menthol, undertaken at two different frequencies. Data revealed the incidence of moderate IAD was decreased in the experimental group (receiving the skin protocol every 6 hours and p.r.n.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 22 publications
1
18
0
2
Order By: Relevance
“…Various topical agents other than zinc oxide have been used in the treatment of dermatitis, which is a significant complication of ileostomy. Sometimes it is not possible to cope with the location of the ileostomy; therefore, it becomes necessary to change the region of the ileostomy [ 7 , 23 , 24 ]. There have been multiple reports presenting the positive effects of ozone therapy in wound healing [ 15 , 17 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various topical agents other than zinc oxide have been used in the treatment of dermatitis, which is a significant complication of ileostomy. Sometimes it is not possible to cope with the location of the ileostomy; therefore, it becomes necessary to change the region of the ileostomy [ 7 , 23 , 24 ]. There have been multiple reports presenting the positive effects of ozone therapy in wound healing [ 15 , 17 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eroded peristomal skin can be treated with a hydrocolloid powder before placing the stoma appliance. Topical and aerosol corticosteroids or antihistamines have been useful in speeding peristomal skin recovery [ 1 , 6 ], while zinc oxide has been used topically in irritant dermatitis treatment and is known for its treatment efficacy [ 7 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eleven studies were identified that specifically addressed IAD in the adult critical care or ICU setting (Bliss et al, ; Bohnenkamp et al, ; Brunner et al, ; Conley et al, ; Coyer et al, ; Driver, ; Ehman et al, ; Eigsti, ; Ma et al, ; Park and Kim, ; Peterson et al, ). Of these 11 studies, 2 studies were published conference abstracts (Ehman et al, ; Peterson et al, ) and 1 study was a conference poster presentation (Bohnenkamp et al, ).…”
Section: Search Strategymentioning
confidence: 99%
“…IAD is a common yet under‐reported phenomenon in the intensive care setting. Of the 11 studies identified, 3 reported IAD prevalence, with ranges from 61·5% to 95% (Bohnenkamp et al, ; Conley et al, ; Peterson et al, ), and one study reported incidence of 29% (Ma et al, ). Furthermore, six studies reported a pre‐intervention IAD incidence range of 23–50% (Bliss et al, ; Brunner et al, ; Coyer et al, ; Driver, ; Ehman et al, ).…”
Section: Prevalence and Incidencementioning
confidence: 99%
See 1 more Smart Citation